Seleção de culturas para produção de alimentos indígenas com propriedades funcionais - Freire, Ana Luiza (2016)
Currently, most probiotic foods present in the food market are based on milk or derivatives. However, the emergence of many allergies and intolerances to this type of raw material have stimulated the development of new products based on cereals and other plants, allowing the provision of the increasing demand for functional non-dairy products. This work aimed at developing non-dairy fermented beverages using Lactic Acid Bacteria (LAB) as culture, with probiotic and yeast potential. For developing a cassava-based beverage, the lines Lactobacillus plantarum CCMA 0743, Torulaspora delbrueckii CCMA 0235 and the commercial probiotic L. acudiohilus LACA 4, were used as starting cultures in simple and cocultivation cultures. The bacterial populations reached near 8.0 log CFU/mL at the end of fermentation. Higher concentrations of residual starch were detected in the simple bacteria cultivations (10.6%), indicating that the co-cultivation with yeast might aid in breaking the starch. The lactic acid was the main organic acid detected (>1.6g/L), with ethanol being inferior to 0.5%, constituting a non-alcoholic beverage. The cultivations containing yeast presented higher antioxidant activity. Sensorial analysis of the beverages indicated the potential for its commercialization, given that the average grade given by consumers for each attribute was around 5, that is, they did not dislike or like the product. A new cereal fermented beverage, based on corn and rice was developed using a mixed culture of L. plantarum CCMA 0743, T. delbrueckii CCMA 0235 and L. acidophilus LACA 4. Two concentrations of prebiotic, 2 and 5% of FOS (frutooligosaccharide), were tested. The growth of probiotic L. acidophilus LACA 4 was favored by the prebiotic at concentrations of 5% and, after time in storage (28 days at 4 o C), it maintained a population of 10 7 CFU/mL. The lactic and acetic acids were the main organic acids detected, around 3.7 g/L and 0.5g/L, respectively. The concentration of ethanol was inferior to 0.5%, indicating a non-alcoholic beverage. A total of 55 volatile compounds, including acids, alcohols, aldehydes, esters, ketones, pyrazines and others, were detected by Gas Chromatography/Mass Spectrometry (GC/MS). The sensorial analysis indicated good acceptance of the beverages by most consumers (≥50%), of which grades ranged from 6 to 9, indicating its potential for commercialization.